Platelets in Advanced Chronic Kidney Disease: Two Sides of the Coin - Lutz, Prof. Dr. med. Jens; Jurk, PD Dr. rer. nat. Kerstin (Seminars in Thrombosis and Hemostasis, 2020)
Rates of thrombosis and bleeding episodes are both increased in patients with advanced chronic kidney disease (CKD). The pathogenic mechanisms of thrombosis in these patients include platelet activation, increased formation of platelet-leukocyte conjugates, and platelet-derived microparticles, as well as effects of uremic toxins on platelets. On the other side of the coin, platelet hyporeactivity mediated by uremic toxins and anemia contributes to the increased bleeding risk in advanced CKD. Platelets also contribute to the inflammatory environment, thus increasing the risk of cardiovascular diseases in these patients. This review provides insights into the altered platelet function in advanced stages of CKD and their relationship with risks of thrombosis and bleeding. Particularly, the effect of dialysis on platelets will be discussed. Furthermore, therapeutic options with respect to thrombotic disorders as well as bleeding in patients with CKD are reviewed.
Keywords: thrombosis; bleeding; hemostasis; anticoagulants; antiplatelet drugs